Addition of Jejunal Lateral Anastomosis is Not Necessary for Gastric-Jejunum Pouch Anastomosis following Distal Gastrectomy: A Propensity-Score Matching Analysis - Guangyu Chen; Jun Wu; Hengdi Zhang; Yi Wen; Guode Luo; Zhenyu Chen; Jun Zhou; Yongkuan Cao (Journal of Investigative Surgery, 2022)
Purpose To make a propensity-score matching analysis on the clinical application of gastric-jejunum pouch anastomosis (GJPA) and continuous jejunal pouch and residual stomach anastomosis combined with jejunal lateral anastomosis (Contin-L). Methods The clinic data of 287 patients who received distal gastrectomy from January 2015 to January 2019 were collected retrospectively. The enrolled patients were divided into the GJPA group and the Contin-L group according to the reconstruction method used. Clinical data and operation complications were analyzed. Results Compared with Contin-L group, the duration of digestive tract reconstruction in the GJPA group was shorter, and the overall cost in the GJPA group was lower. No obvious intergroup differences were found in other intraoperative data, early surgical outcomes, incidence rates of reflux gastritis, anastomotic ulcer, postoperative nutritional and hematological indicators. The postoperative subjective feelings in the GJPA group were similar with those in the Contin-L groups. Conclusion Addition of jejunal lateral anastomosis is not necessary for GJPA following distal gastrectomy.